Pengaruh Jamur Trichoderma dan Pupuk Kandang Sapi terhadap Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - M. Abdul Haris Sinaga; Achmad Himawan; Elizabeth Nanik Kristalisasi (Program Studi Agroteknologi INSTIPER, 2022)
The aim of this research are to know significance interaction between Trichoderma and cow manure for oil palm pre-nursery seedlings growth, to know the best dosage of Trichoderma for oil palm pre-nursery seedlings growth, and to know the best dosage of cow manure for oil palm pre-nursery seedlings growth. This research was conducted at education and research site (KP2) Institut Pertanian Stiper Yogyakarta, Maguwoharjo, Depok, Sleman, Yogyakarta Special Region. Research location altitude is 118 m asl. This research was carried out in April – June 2021. This research used Completed Random Design that consist of 2 factors. First factor was Trichoderma dosages namely 0 (control), 20, 40, and 60 g/polybag. Second factor was cow manure dosages namely 0 (control), 200, 600, and 1,000 g/polybag. The results showed that there is no significance interaction between Trichoderma and cow manure for all of parameters of oil palm pre-nursery seedlings growth. Trichoderma dosage 20 g/polybag is the best for stem diameter, fresh weight canopy, and dry weight roots parameters. Cow manure dosage 200 g/polybag is the best for seedlings height, leaf number, fresh weight canopy, dry weight canopy, fresh weight roots, and leaf area parameters.